A Journey to Inner Africa - Kovalevsky, Egor (Amherst College Press, 2020)
In 1847, Russian military engineer and diplomat Egor Petrovich Kovalevsky embarked on a journey through what is today Egypt, Sudan, Eritrea, and Ethiopia, recording his impressions of a region in flux. Invited by Egyptian ruler Mohammed Ali to look for gold and construct mines in the area between the Blue and White Nile, Kovalevsky captured the social milieu of both elites and ordinary people as well as compiled a rich record of the Upper Nile's climate and natural resources. A Journey to Inner Africa, masterfully translated into English for the first time by Anna Aslanyan, is both a tale of encounter between Russia and northern Africa and an important document in the history and development of the Russian imperial project.